A novel Peng's test in reducing bile leakage after partial hepatectomy for hepatocellular carcinoma: From an animal study to a clinical cohort Propensity score matching comparative study. (August 2022) - Mo, Shutian; He, Yongfei; Zhu, Guangzhi; Su, Hao; Han, Chuangye; Ye, Xinping; Liao, Xiwen; Yang, Chengkun; Liang, Tianyi; Chen, Zijun; Wei, Yongguang; Wei, Zhongliu; et al.
Abstract: Background: Bile leakage (BL) is a common complication of partial hepatectomy for hepatocellular carcinoma (HCC). However, various intraoperative approaches to detect BL have not been widely accepted owing to uncertainty in their treatment effectiveness and complexity of use. Materials and methods: A novel BL-detection approach (Peng's test) was developed in a swine model to determine the pressures generated in the gallbladder and common bile duct (CBD) during the test. A comparative study was then conducted on a prospective cohort of patients using Peng's test versus a retrospective historical cohort patient group using the White Gauze test in partial hepatectomy for HCC. Propensity score matching (PSM) was performed in a 1:1 ratio to balance confounding factors. Results: The maximum pressures with methylene blue injection in the gallbladder and CBD without Pringle's maneuver in the four swines were 103.8 ± 11.8 and 42.3 ± 6.1, respectively. After Pringle's maneuver, 32.0 ± 6.8 mL methylene blue injection led to a maximum pressure in the CBD of 85.3 ± 9.5 cmH2 O. The pressures in CBD were 25.8 ± 3.3 and 86.0 ± 9.9 cmH2 O when BL appeared at small bile ducts and around the ligation sites, respectively. Of the 206 patients enrolled in the historical control group, 31 (15.0%) developed BL, while of the 54 patients in the study group, only 1 developed grade A BL. The number of BL detected by the routine white gauze test in the control group was significantly lower than that in the study group (Z = −3.002, P  = 0.003). After PSM, the incidence of BL in the control group and grade B/C BL was 20.4% and 11.1%, respectively. The corresponding incidences in the study group were 1.9% (χ 2  = 7.594, P  = 0.006) and 0% ( P  = 0.027), respectively. The length of hospital stay in the study group was significantly reduced (Z = −6.048, P  < 0.001). Conclusion: Peng's test for intraoperative BL detection is safe and effective in reducing BL after hepatectomy. Highlights: Peng's test is incubation in the gallbladder instead of the CBD. Peng's test could safely and effectively reduce bile leakage. The association between pressure in gallbladder and in the CBD was explored by animal model. The association between CBD pressure and bile leakage was explored by animal model.